Can the soil seed bank of Rumex obtusifolius in productive grasslands be explained by management and soil properties? - Matthias Suter; Julie Klötzli; Deborah Beaumont; Aleš Kolmanič; Robert Leskovšek; Urs Schaffner; Jonathan Storkey; Andreas Lüscher (PLoS ONE)
Rumex obtusifolius is a problematic weed in temperate grasslands worldwide as it decreases yield and nutritional value of forage. Because the species can recruit from the seed bank, we determined the effect of management and soil properties on the soil seed bank of R. obtusifolius in intensively managed, permanent grasslands in Switzerland (CH), Slovenia (SI), and United Kingdom (UK). Following a paired case-control design, soil cores were taken from the topsoil of grassland with a high density of R. obtusifolius plants (cases) and from nearby parcels with very low R. obtusifolius density (controls). Data on grassland management, soil nutrients, pH, soil texture, and density of R. obtusifolius plants were also collected. Seeds in the soil were germinated under optimal conditions in a glasshouse. The number of germinated seeds of R. obtusifolius in case parcels was 866 ±152 m-2 (CH, mean ±SE), 628 ±183 m-2 (SI), and 752 ±183 m-2 (UK), with no significant difference among countries. Densities in individual case parcels ranged from 0 up to approximately 3000 seeds m-2 (each country). Control parcels had significantly fewer seeds, with a mean of 51 ±18, 75 ±52, and 98 ±52 seeds m-2 in CH, SI, and UK, respectively, and a range between 0 and up to 1000 seeds m-2. Across countries, variables explaining variation in the soil seed bank of R. obtusifolius in case parcels were soil pH (negative relation), silt content (negative), land-use intensity (negative), and aboveground R. obtusifolius plant density (positive). Because a large soil seed bank can sustain grassland infestation with R. obtusifolius, management strategies to control the species should target the reduction in the density of mature plants, prevention of the species' seed production and dispersal, as well as the regulation of the soil pH to a range optimal for forage production.